INFORMATION AND ANALYTICAL SYSTEM FOR SUPPORTING THE EDUCATIONAL ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS - VDOVENKO, Nataliia; MARHASOVA, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the conceptual foundations and practical aspects of implementing information and analytical systems (IAS) to support the educational activities of higher education institutions (HEIs) in Ukraine amid the ongoing digital transformation. The author substantiates the strategic importance of IAS as a central component of smart university governance, not only automating routine administrative functions but also enabling evidence-based decision-making grounded in real-time data analytics. A structural and functional model of IAS is proposed, with detailed descriptions of its core modules, including student records management, academic workload planning, analytics and reporting, quality assurance, financial tracking, and external system integrations. The study highlights the key challenges facing Ukrainian universities in the digitalization process—fragmented IT infrastructure, insufficient digital competence among staff, limited financial resources, and lack of a unified national policy for digital platform deployment in education governance. Comparative analysis with EU universities reveals a significant lag in the integration level of digital systems, while simultaneously pointing to the high development potential of Ukrainian HEIs, given the right strategic support and investments. Based on international best practices and Ukrainian case studies, the article identifies promising directions for further development of IAS: the implementation of artificial intelligence and Learning Analytics tools, the personalization of educational trajectories, the development of cloud-based infrastructure, and the standardization of data protection and interoperability protocols. The research concludes that IAS should be viewed not merely as a technical tool but as a conceptual foundation for building modern, competitive, and transparent universities capable of meeting the challenges of the digital era and participating actively in the global higher education ecosystem.